Capacity of Active Power Reserve for Frequency Control Enhanced by Distributed Generators - Rueda-Medina, Augusto C. [UNESP]; Padilha-Feltrin, Antonio [UNESP]; Mantovani, J. R. S. [UNESP]; IEEE (Ieee, 2013)
Usually, ancillary services are provided by large conventional generators; however, with the growing interest in distributed generation to satisfy energy and environmental requirements, it seems reasonable to assume that these services could also be provided by distributed generators in an economical and efficient way. In this paper, a proposal for enhancement of the capacity of active power reserve for frequency control using distributed generators is presented. The goal is to minimize the payments done by the transmission system operator to conventional and distributed generators for this ancillary service and for the energy needed to satisfy loads and system losses, subject to a set of constraints. In order to perform analysis, the proposal was implemented using data of the IEEE 30-bus transmission test system. Comparisons were performed considering conventional generators without and with distributed generators installed in the system.
Keywords: Conventional generators; distributed generators; active power reserve for frequency control; costs minimization